Incremental Validity Of The Diagnostic Criteria For Psychosomatic Research – Revised (DCPR-R) To Clinical Assessment In Primary Care. (September 2020) - Guidi, Jenny; Piolanti, Antonio; Berrocal, Carmen; Gostoli, Sara; Carrozzino, Danilo
Highlights: Clinically valid assessment tools of psychosocial aspects in primary care are needed. The DCPR-R identify psychosocial factors that would be undetected using the DSM-5. The DCPR-R increase the prediction of psychosocial functioning in primary care. Abstract: Psychosocial problems are highly prevalent among primary care (PC) patients, but they often remain undetected using traditional classification systems. The aim of the present study was to test the incremental validity of the revised version of the Diagnostic Criteria for Psychosomatic Research (DCPR-R), in addition to standard psychiatric assessment based on DSM-5, with regard to the prediction of psychosocial functioning of PC patients. Two-hundred PC patients were consecutively recruited. A comprehensive assessment was performed using two clinical interviews and three self-rating questionnaires (the PsychoSocial Index [PSI], the Short-Form Health Survey [SF-12] and the Illness Attitude Scales [IAS]) for the assessment of psychopathology and psychosocial functioning. Adding the DCPR-R to DSM-5, the amount of explained variance significantly increased by 9% to 16% in the PSI subscales, by 13% in the SF-12 mental component summary, and by 2% to 6% in the IAS scales. The joint use of DCPR-R and DSM-5 thus significantly increased the prediction of psychosocial functioning of primary care patients. These findings further support the use of the DCPR-R in PC settings, particularly in patients who do not satisfy DSM-5 criteria and yet present with high psychological distress, maladaptive illness behavior, impaired psychological well-being and quality of life.